Panorama de mujeres documentalistas árabes - Dra. Carolina BRACCO (Fonseca, Journal of Communication, 2023)
This paper provides a general overview of women documentary filmmakers in the Arab world. The text intends to elaborate on these aspects in relation to the condition of women’s roles, their participation in the public sphere and their participation in audiovisual production.